Enhancing Snow Cover Monitoring: A Modified Cloud Removal Methodology for MODIS Data in the Tapovan Vishnugad Basin - Gopika Vijayalekshmi; N. K. Goel; Manohar Arora (Journal of the Indian Society of Remote Sensing, 2026)

Advancing Hematopoietic Stem Cell Research: The Impact of Bioengineered 3D Bone Marrow Niches - Hridhya K. Sidharthan; Mansi Goel; Manoj Unni; Neeraj Sidharthan; Binulal N. Sathy (Stem Cell Reviews and Reports, 2026)

Cloudburst or hybrid phenomenon? Dissecting the Dharali flood disaster of 2025 - Gopika Vijayalekshmi; N. K. Goel; Manohar Arora; M. L. Sharma; R. Unni Narayanan; R. K. Vishnoi (Hydrological Sciences Journal, 2026)

Short-range monsoon rainfall forecasting using multi-model ensembles and analysis of threshold-based rainfall verification - Suman Gurjar; N. K. Goel; Manohar Arora; M. K. Goel (Theoretical and Applied Climatology, 2026)

Peak Rainfall Seasonality and Its Changes Influenced by Monsoons in India - Chingka Kalai; N. K. Goel (International Journal of Climatology, 2025)
Seasonality of peak rainfall finds its application in several water resource activities such as deciding the timing of agriculture, regulation of water control structure, predicting the timing of floods; and understanding the lag between rainfall and floods. In a country like India, rainfall (which is the primary source of water) is influenced by different monsoon patterns, causing a disparity in its seasonality, thus, understanding the timing of the peak rainfall and its changes becomes crucial for water resources management. Here, the circular statistical approach is employed to understand the characteristics of peak rainfall (PRF) seasonality in India. It is observed that the western coast and central parts are influenced by the southwest monsoon (June–September) yielding strong seasonality. While, dominance of the northeast monsoon (October–December) is observed along the eastern coast with moderate to strong seasonality moving from north to south. The region lying between the west and the east coast is influenced by both southwest and northeast monsoons yielding bimodal seasonality of PRF. Also, northeast India is found to be influenced by both monsoon patterns. A weak seasonality of PRF is observed in the northern parts that are influenced by several factors like southwest monsoon, northeast monsoon, and snowfall (December–April). Three existing tests along with the proposed modified versions of Pettitt and Mann–Kendall tests are applied to detect changes in the seasonality of PRF. Grids identified with changes at 5% and 10% significance levels considering these tests showed significant differences in mean date and resultant length, and gradual shift in the dates of PRF. The analysis demonstrates the necessity of distinct water resource planning for different Indian regions. Also, changes in the timings of PRF implicate the effect of climate change, which demonstrates the need for a revision in water resources planning and management.

Spatial Heterogeneity in Health Risk Assessment of Heavy Metals During North-East Monsoon and South-West Monsoon over India - Martina Rani; Sakshi Ahlawat; N. Vijayan; Lokesh Yadav; Tirthankar Banerjee; Abhijeet Chatterjee; Manpreet Singh Bhatti; Trupti Das; Amit Dhir; Sangita Goel; Altaf Husain Khan; Ravindra Khaiwal; et al. (Aerosol Science and Engineering, 2025)

Comprehensive analysis of hydrological and glacial dynamics in the Himalayas: addressing glacial lake outburst flood risks in hydropower development - Isly Issac; N. K. Goel; Wolfgang Schwanghart; Manohar Arora (Natural Hazards, 2025)

Remediation of dye wastewater using radiation-functionalized polyurethane foam: A viable waste to wealth conversion strategy - N. K. Goel; N. Misra; S. A. Shelkar; S. Rawat; V. Kumar (International Journal of Environmental Science and Technology, 2024)

Plasma polymerized functional supermagnetic Fe3O4 nanostructured templates for laccase immobilization: A robust catalytic system for bio-inspired dye degradation - Swarnima Rawat; Nilanjal Misra; Sher Singh Meena; Shubhangi S. Shelkar; Naveen Kumar N; Narender Kumar Goel; Virendra Kumar (Environmental Science and Pollution Research, 2022)

Artificial intelligence enabled intrusion detection systems for cognitive cyber-physical systems in industry 4.0 environment - Manal Abdullah Alohali; Fahd N. Al-Wesabi; Anwer Mustafa Hilal; Shalini Goel; Deepak Gupta; Ashish Khanna (Cognitive Neurodynamics, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Trend analysis of hydro-meteorological parameters in the Jhelum River basin, North Western Himalayas - Sheikh Umar; M. A. Lone; N. K. Goel; Mohammad Zakwan (Theoretical and Applied Climatology, 2022)

The Built Environment and Health in Low- and Middle-Income Countries: a Review on Quantitative Health Impact Assessments - M. Thondoo; R. Goel; L. Tatah; N. Naraynen; J. Woodcock; Mark Nieuwenhuijsen (Current Environmental Health Reports, 2022)

A novel four-step feature selection technique for diabetic retinopathy grading - N. Jagan Mohan; R. Murugan; Tripti Goel; Seyedali Mirjalili; Parthapratim Roy (Physical and Engineering Sciences in Medicine, 2021)

Modeling of peak discharges and frequency analysis of floods on the Jhelum river, North Western Himalayas - Sheikh Umar; M. A. Lone; N. K. Goel (Modeling Earth Systems and Environment, 2021)

Modeling of annual rainfall extremes in the Jhelum River basin, North Western Himalayas - Sheikh Umar; M. A. Lone; N. K. Goel (Sustainable Water Resources Management, 2021)

Development of a set of three real-time loop-mediated isothermal amplification (LAMP) assays for detection of Bacillus anthracis, the causative agent of anthrax - Swati Banger; Vijai Pal; N. K. Tripathi; A. K. Goel (Folia Microbiologica, 2021)

End Point Multiplex PCR for Diagnosis of Haemoprotozoan Diseases in Cattle - Gaurav Charaya; N. K. Rakha; Aman Kumar; Sushila Maan; Parveen Goel (Acta Parasitologica, 2021)

Correction to: Evaluation and ranking of different gridded precipitation datasets for Satluj River basin using compromise programming and f-TOPSIS - Bratati Chowdhury; N. K. Goel; M. Arora (Theoretical and Applied Climatology, 2021)

Evaluation and ranking of different gridded precipitation datasets for Satluj River basin using compromise programming and f-TOPSIS - Bratati Chowdhury; N. K. Goel; M. Arora (Theoretical and Applied Climatology, 2021)

Protein Kinase Inhibitors Arrested the In-Vitro Growth of Theileria equi - Jyotika Yadav; Praveen Goel; Kruti Debnath Mandal; Rahul Yadav; Naveen Kumar; Rajender Kumar; B. N. Tripathi; Sanjay Kumar (Acta Parasitologica, 2020)

Influence of fin density on the performance of an impinging jet with fins type solar air heater - Abhishek Kumar Goel; S. N. Singh (Environment, Development and Sustainability, 2020)

Experimental study of heat transfer characteristics of an impinging jet solar air heater with fins - Abhishek Kumar Goel; S. N. Singh (Environment, Development and Sustainability, 2020)

Prediction of upslope movement of Rhododendron arboreum in Western Himalaya - Sri N. S. Veera; Rajendra M. Panda; Mukunda D. Behera; Shailendra Goel; Partha S. Roy; Saroj K. Barik (Tropical Ecology, 2019)

Prediction of Ground Behaviour for Rock Tunnelling - R. D. Dwivedi; R. K. Goel; M. Singh; M. N. Viladkar; P. K. Singh (Rock Mechanics and Rock Engineering, 2019)

Stability of Vaccines - N. Dumpa; K. Goel; Yuhan Guo; H. McFall; Amit Raviraj Pillai; Ashay Shukla; M. A. Repka; S. Narasimha Murthy (AAPS PharmSciTech, 2019)

Cytogenetic and molecular evidences revealing genomic changes after autopolyploidization: a case study of synthetic autotetraploid Phlox drummondii Hook - Tanvir H. Dar; Soom N. Raina; Shailendra Goel (Physiology and Molecular Biology of Plants, 2017)

Matrix-assisted laser desorption ionization time of flight mass spectrometry (MALDI-TOF MS) for rapid identification of micro-organisms in the routine clinical microbiology laboratory - C. Wattal; J. K. Oberoi; N. Goel; R. Raveendran; S. Khanna (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

ISSR markers for gender identification and genetic diagnosis of Hippophae rhamnoides ssp. turkestanica growing at high altitudes in Ladakh region (Jammu and Kashmir) - Kamal Das; Showkat Hussain Ganie; Yash Mangla; Tanvir-Ul-Hassan Dar; Manju Chaudhary; Rakesh Kumar Thakur; Rajesh Tandon; S. N. Raina; Shailendra Goel (Protoplasma, 2017)

Protein–protein and DNA–protein interactions mediate induction of defense genes by fruit extract of Azadirachta indica A. Juss. in Solanum lycopersicum L. - V. Bhuvaneshwari; N. Goel; P. K. Paul (Plant Cell Reports, 2015)

Unraveling the cytotoxic potential of Temozolomide loaded into PLGA nanoparticles - Darshana S Jain; Rajani B Athawale; Amrita N Bajaj; Shruti S Shrikhande; Peeyush N Goel; Yuvraj Nikam; Rajiv P Gude (DARU Journal of Pharmaceutical Sciences, 2014)
Background Nanotechnology has received great attention since a decade for the treatment of different varieties of cancer. However, there is a limited data available on the cytotoxic potential of Temozolomide (TMZ) formulations. In the current research work, an attempt has been made to understand the anti-metastatic effect of the drug after loading into PLGA nanoparticles against C6 glioma cells. Nanoparticles were prepared using solvent diffusion method and were characterized for size and morphology. Diffusion of the drug from the nanoparticles was studied by dialysis method. The designed nanoparticles were also assessed for cellular uptake using confocal microscopy and flow cytometry. Results PLGA nanoparticles caused a sustained release of the drug and showed a higher cellular uptake. The drug formulations also affected the cellular proliferation and motility. Conclusion PLGA coated nanoparticles prolong the activity of the loaded drug while retaining the anti-metastatic activity.

Is an Alternative Drug Delivery System Needed for Docetaxel? The Role of Controlling Epimerization in Formulations and Beyond - Arehalli S. Manjappa; Peeyush N. Goel; Makam P. Vekataraju; Kesarla S. Rajesh; Kinjal Makwana; Mukesh Ukawala; Yuvraj Nikam; Rajiv P. Gude; Rayasa S. Ramachandra Murthy (Pharmaceutical Research, 2013)

Effect of angiotensin II on spatial memory, cerebral blood flow, cholinergic neurotransmission, and brain derived neurotrophic factor in rats - Santoshkumar Tota; Ruby Goel; Shakti Deep Pachauri; Rajasekar N.; Abul Kalam Najmi; Kashif Hanif; Chandishwar Nath (Psychopharmacology, 2013)

Surface Plasmon Resonance Biosensor for Detection of Bacillus anthracis, the Causative Agent of Anthrax from Soil Samples Targeting Protective Antigen - N. Ghosh; G. Gupta; M. Boopathi; V. Pal; A. K. Singh; N. Gopalan; A. K. Goel (Indian Journal of Microbiology, 2013)

Genetic structure and diversity of India hybrid tea - S. N. Raina; P. S. Ahuja; R. K. Sharma; S. C. Das; P. Bhardwaj; R. Negi; V. Sharma; S. S. Singh; R. K. Sud; R. K. Kalia; V. Pandey; J. Banik; et al. (Genetic Resources and Crop Evolution, 2012)

Unravelling the antimetastatic potential of pentoxifylline, a methylxanthine derivative in human MDA-MB-231 breast cancer cells - Peeyush N. Goel; R. P. Gude (Molecular and Cellular Biochemistry, 2011)

Limitation of 90 m SRTM DEM in drainage network delineation using D8 method—a case study in flat terrain of Bangladesh - M. M. Rahman; D. S. Arya; N. K. Goel (Applied Geomatics, 2010)

Development of isopluvial map using L-moment approach for Tehri-Garhwal Himalaya - S. Sarkar; N. K. Goel; B. S. Mathur (Stochastic Environmental Research and Risk Assessment, 2010)

Analysis of historical changes in rainfall in the Indian Himalayas - Ashoke Basistha; D. S. Arya; N. K. Goel (International Journal of Climatology, 2009)
The present study attempts to explore changes in rainfall pattern in the Indian Himalayas during 20th century using 80‐year data from 30 rain gauge stations maintained by the India Meteorological Department (IMD). Modified Mann–Kendall test (MMK) was applied to detect trend, and Pettitt–Mann–Whitney (PMW) test was employed to detect possible shift. Implication of the change is discussed in terms of percentage change over mean. The results show that the most probable year of change in annual as well as monsoon rainfall in the region is 1964. There was an increasing trend upto 1964 (corroborating with all India and nearby plains), followed by a decreasing trend in 1965–1980 (exclusive to this region). In the entire region, changes are most conspicuous over the Shivaliks and the southern part of the Lesser Himalayas. Copyright © 2008 Royal Meteorological Society

In vitro manipulations in St. John’s wort (Hypericum perforatum L.) for incessant and scale up micropropagation using adventitious roots in liquid medium and assessment of clonal fidelity using RAPD analysis - Manoj K. Goel; A. K. Kukreja; N. S. Bisht (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)

Spatial Distribution of Rainfall in Indian Himalayas – A Case Study of Uttarakhand Region - Ashoke Basistha; D. S. Arya; N. K. Goel (Water Resources Management, 2008)

Climate Variability Influences on Hydrological Responses of a Large Himalayan Basin - Manohar Arora; Pratap Singh; N. K. Goel; R. D. Singh (Water Resources Management, 2008)

Mapping of adult plant stripe rust resistance genes in diploid A genome wheat species and their transfer to bread wheat - Parveen Chhuneja; Satinder Kaur; Tosh Garg; Meenu Ghai; Simarjit Kaur; M. Prashar; N. S. Bains; R. K. Goel; Beat Keller; H. S. Dhaliwal; Kuldeep Singh (Theoretical and Applied Genetics, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Bacterial laccases - P. Sharma; R. Goel; N. Capalash (World Journal of Microbiology and Biotechnology, 2007)

Spatial Distribution and Seasonal Variability of Rainfall in a Mountainous Basin in the Himalayan Region - Manohar Arora; Pratap Singh; N. K. Goel; R. D. Singh (Water Resources Management, 2006)

Interaction of gut microflora with tannins in feeds - Gunjan Goel; A. K. Puniya; C. N. Aguilar; Kishan Singh (The Science of Nature, 2005)

Radioprotective mechanism of Podophyllum hexandrum during spermatogenesis - N. Samanta; K. Kannan; M. Bala; H. C. Goel (Molecular and Cellular Biochemistry, 2004)

Immunomodulatory and cytoprotective role of RP-1 in γ-irradiated mice - H.C. Goel; P.K. Agrawala; V. Pathania; N. Malhotra (Molecular and Cellular Biochemistry, 2003)

Lysophospholipids do not directly modulate Na+-H+ exchange - Danny P. Goel; David A. Ford; Grant N. Pierce (Molecular and Cellular Biochemistry, 2003)

Individual and combined effect of (±)-α-hydrastine and (±)-β-hydrastine on spore germination of some fungi - M. Goel; U. P. Singh; R. N. Jha; V. B. Pandey; M. B. Pandey (Folia Microbiologica, 2003)

The ability of an HSV strain to initiate zosteriform spread correlates with its neuroinvasive disease potential - N. Goel; H. Mao; Q. Rong; J. J. Docherty; D. Zimmerman; K. S. Rosenthal (Archives of Virology, 2002)

Physical mapping of 18S-5.8S-26S and 5S ribosomal RNA gene families in three important vetches (Vicia species) and their allied taxa constituting three species complexes - S. N. Raina; Y. Mukai; K. Kawaguchi; S. Goel; A. Jain (Theoretical and Applied Genetics, 2001)

Evidence for new nuclear and mitochondrial genome organizations among high-frequency somatic embryogenesis-derived plants of allotetraploid Coffea arabica L. (Rubiaceae) - V. Rani; K. P. Singh; B. Shiran; S. Nandy; S. Goel; R. M. Devarumath; H. L. Sreenath; S. N. Raina (Plant Cell Reports, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)